PERAN MOTIVASI KERJA DALAM MENJEMBATANI ANTARA KARAKTERISTIK PEKERJAAN DAN KOMPENSASI TERHADAP KINERJA PEGAWAI NON ASN DI KECAMATAN PAKIS AJI, JEPARA - Indra Hary Tri Setyawan; Pahlawansyah Harahap (Jurnal Riset Ekonomi dan Bisnis, 2019)
Tujuan dalam penelitian ini adalah untuk menganalisa pengaruh karakteristik pekerjaan dan kompensasi terhadap motivasi kerja, serta menganalisa pengaruh karakteristik pekerjaan, kompensasi dan motivasi kerja terhadap kinerja pegawai.Populasi dalam penelitian ini adalah seluruh pegawai kelurahan non ASN di Kecamatan Pakis Aji, Jepara yang berjumlah 101 dengan metode penentuan sampel yang dipergunakan adalah sensus sampling, yang artinya keseluruhan jumlah populasi dijadikan sampel penelitian. Alat analisis menggunakan SEM (struktur equitions modeling)Hasil penelitian membuktikan bahwa karakteristik pekerjaan dan kompensasi berpengaruh signifikan terhadap motivasi kerja. Karakteristik pekerjaan dan kompensasi tidak berpengaruh terhadap kinerja pegawai. Motivasi kerja berpengaruh signifikan terhadap kinerja pegawai. The purpose of this study is to analyze the effect of job characteristics and compensation on work motivation, and analyze the influence of job characteristics, compensation and work motivation on employee performance.The population in this study were all employees of non-ASN urban villages in Pakis Aji Subdistrict, Jepara, which numbered 101 with the method of determining the sample used was census sampling, which means that the total population was used as the research sample. Analysis tools using SEM (structural modeling equations)The results of the study prove that job characteristics and compensation have a significant effect on work motivation. Job characteristics and compensation do not affect employee performance. Work motivation has a significant effect on employee performance.The purpose of this study is to analyze the effect of job characteristics and compensation on work motivation, and analyze the influence of job characteristics, compensation and work motivation on employee performance.               The population in this study were all employees of non-ASN urban villages in Pakis Aji Subdistrict, Jepara, which numbered 101 with the method of determining the sample used was census sampling, which means that the total population was used as the research sample. Analysis tools using SEM (structural modeling equations)            The results of the study prove that job characteristics and compensation have a significant effect on work motivation. Job characteristics and compensation do not affect employee performance. Work motivation has a significant effect on employee performance.